Carbonic anhydrase activity of coupling factor CF1 isolated from spinach chloroplasts - Semenihin, A.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
The aim of the work was to determine the carbonic anhydrase (CA) activity of coupling factor CF1 – catalytic part of ATPsyntase complex from chloroplasts. The purity of CF1 prepared by the standard method from spinach chloroplasts was tested by electrophoretic analysis under native and denaturing conditions in the Laemmli system. The properties of the obtained preparation correspond to the literature data for CF1: polypeptide consists of 5 types of subunits with appropriate molecular masses and catalyzes ATP hydrolysis in the presence of Mg2+ or Ca2+. The analysis of the isolated preparation of CF1 in the native gel with a pH indicator bromothymol blue was shown that, when the gel was immersed in a buffer solution saturated with CO2, the color of the polypeptide zone with CF1 changed from blue to yellow, indicating the activation of carbon dioxide conversion into bicarbonate and protons. Data obtained in this study allow us to conclude that the isolated CF1 along with ATPase has also the carbonic anhydrase activity. A possible role of the CA-activity in the mechanisms of ATP synthesis-hydrolysis catalyzed by ATP synthase is discussed.